2000
DOI: 10.1081/jdi-100100885
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of Hematocrit in Hemodialysis Patients With Cardiac Disease Does Not Increase Blood Pressure

Abstract: It is possible to increase hematocrit to normal levels in hemodialysis with the administration of Epoetin alfa. The increase in hematocrit from 30+/-3% to 42+/-3% is not associated with increased blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 13 publications
2
25
0
Order By: Relevance
“…Standardized techniques were used by several studies that were included in this review. Erturk et al (37) did not observe substantial differences in the recordings when using a standardized technique, but others (23,30,33,34,36,40) did. Studies that used the standardized measurements had as much variability in the difference between pre/postdialysis BP and ambulatory measurements as did nonstandardized studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standardized techniques were used by several studies that were included in this review. Erturk et al (37) did not observe substantial differences in the recordings when using a standardized technique, but others (23,30,33,34,36,40) did. Studies that used the standardized measurements had as much variability in the difference between pre/postdialysis BP and ambulatory measurements as did nonstandardized studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies enrolled consecutive or random patients (24,28 -30), but some selected normotensive individuals only (31) or hypertensive individuals only (21,25) or required the availability of a good acoustic window for performance of echocardiograms (32). Three trials had prespecified hematocrit cutoffs for ABP monitoring as a result of participation in anemia correction trials (23,33,34).…”
Section: Qualitative Analysismentioning
confidence: 99%
“…Overall, the achieved Hb values of the experimental arms in this group of trials were in the range of 119 to 150 g/L and the achieved Hb values of the control arm were in the range of 90 to 120 g/L. Of the seven studies in this group, the Besarab et al (16), Berns et al (26), and Conlon et al (28) trials enrolled patients with severe cardiovascular disease (congestive heart failure or ischemic heart disease). The Besarab et al (16) trial was terminated at the third interim analysis when differences in mortality between the groups were recognized as sufficient to make it very unlikely that continuation of the study would reveal a benefit for the higher Hb target group.…”
Section: Trial Characteristicsmentioning
confidence: 99%
“…There is great variability in response to ESA treatment (67,70,71). Some patients require small dosages to achieve Hb targets; others require much higher dosages.…”
Section: Role Of Epo Responsivenessmentioning
confidence: 99%
“…However no detailed data on changes in antihypertensive regimens for the two groups were provided. In the second study reported (67), during the first 28 wk of the ramp up, changes in antihypertensive regimen were needed in only 15% of patients, and the frequency was identical in both groups; however, all investigators were encouraged to make downward adjustments in dry weight, if possible, as Hb increased (A.B. personal observation, 1994 -1995).…”
Section: Role Of Hypertensionmentioning
confidence: 99%